Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1182/bloodadvances.2019000219
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of CAR T cells harboring lentivector integration in the CBL gene following anti-CD22 CAR T-cell therapy

Abstract: Key Points Reexpansion of CAR T cells led to further investigations which confirmed the clonal nature of this expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 31 publications
(36 reference statements)
0
67
0
Order By: Relevance
“…Almost no genotoxic effects from gene transfer into differentiated cells, including T cells, are known. Only a few cases of virus-mediated transformation in patients treated with genetically modified T cells have been reported so far [65][66][67]. A lentiviral vector-mediated insertion of the CAR transgene was observed in a CLL patient treated with CD19-specific CART cells, leading to a disruption of the methylcytosine dioxygenase TET2 gene [65].…”
Section: Viral Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost no genotoxic effects from gene transfer into differentiated cells, including T cells, are known. Only a few cases of virus-mediated transformation in patients treated with genetically modified T cells have been reported so far [65][66][67]. A lentiviral vector-mediated insertion of the CAR transgene was observed in a CLL patient treated with CD19-specific CART cells, leading to a disruption of the methylcytosine dioxygenase TET2 gene [65].…”
Section: Viral Transductionmentioning
confidence: 99%
“…Although insertional mutagenesis is undesirable, the described TET2 modification could be used for an optimization of CART cell therapy. An additional case of clonal expansion was seen in a patient that was treated with CD22-specific CART cells caused by lentiviral vector-mediated integration in the CBL gene that is important for the regulation of T cell responses [66]. Furthermore, insertional mutagenesis led to tumor escape in a patient relapsing after treatment with CD19-specific CART cells with a CD19-negative leukemia [67].…”
Section: Viral Transductionmentioning
confidence: 99%
“…Similarly, vector insertions in CAR T cells might trigger clonal expansions of genetically modified cells, showing dramatic in vivo expansion of a single clone. As documented in CAR T cell trials using viral vectors, vector insertion within the CBL oncogene and disruption of the normal TET2 allele were reported(56,57). Despite a recent study has suggested that vector insertions might promote CAR T clonal expansion which correlates with positive outcome (58), we did not find any evidence that SB insertions in our trial have triggered any clonal dominance, no selection of genes targeted by CIS which have been associated with potential leukemogenic insertional events in preclinical and clinical gene therapy.…”
mentioning
confidence: 91%
“…Another study points out that the lentivirus used to establish anti CD22 CAR-T cells was associated with clonal expansion of cells harboring provirus insertion in the CBL (casitas B-lineage lymphoma) proto-oncogene, though the patients’ ALL resolved and the CAR-T cells ceased the expansion. A subsequent CD22-negative relapse suggests a mechanism independent of CAR-T cell function [ 120 ]. This indicates, so far, that insertional mutagenesis can generate relevant functional data indicating genome locations where CAR insertion impacts T cell expansion.…”
Section: New Routes For Gene Transfer: Bringing the Car To The Celmentioning
confidence: 99%